2014
DOI: 10.12965/jer.140147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on visual perception and visual motor integration in Korean adults

Abstract: This study investigated age-related changes of cognitive function in Korean adults using the Korean-Developmental Test of Visual Perception-2 (K-DTVP-2) and the Visual Motor Integration-3rd Revision (VMI-3R) test, and determined the main factors influencing VP and VMI in older adults. For this research, 139 adults for the K-DTVP-2 and 192 adults for the VMI-3R, from a total of 283 participants, were randomly and separately recruited in province, Korea. The present study showed that the mean score of the K-DTVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Serious changes occur in the perceptual-motor system with increasing age. Perceptualmotor adaptability and hand-eye coordination decrease with increasing age [18,19,48,49]. Some studies have reported that changes in visual functions, particularly a decrease in motor visual integration, are the first significant sign of AD [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious changes occur in the perceptual-motor system with increasing age. Perceptualmotor adaptability and hand-eye coordination decrease with increasing age [18,19,48,49]. Some studies have reported that changes in visual functions, particularly a decrease in motor visual integration, are the first significant sign of AD [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, some studies found that the visual-motor disintegration was related to MCI [14][15][16][17]. With increasing age, adaptive visual-motor coordination (hand-eye coordination) decreases [18,19]. In Iran, a study showed that the elderly with AD have poor perfor-mance on the Bender-Gestalt test in which higher rates of error are a sign of brain damage in these patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Memory, the ability to restore and recall information such as words, faces, and events [1], and visual-motor integration, the ability to integrate physical movement with sensory information from visual perception [2], are most susceptible to changes at the early stage of cognitive decline [3,4]. Decline in memory and visual-motor integration causes various problems in performing almost all activities of daily living, such as saying words and names in conversation, remembering a phone number or a promise, finding things, writing and drawing, or changing positions.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional ity of life because it coordinates and executes physical activities along with visual perception and commands from the central nervous system for daily living activities such as eating, walking, and writing [4]. The concept of visual-motor integration was originally developed to distinguish learning difficulties in children' s cognitive development and to improve their academic achievement and adaptation in school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation